The challenge of correctly reporting hormones content and secretion in isolated human islets - Henquin, Jean-Claude (Mol Metab, 2019)
BACKGROUND: An increased access of research laboratories to isolated human islets has improved our understanding of the biology of the endocrine pancreas and hence the mechanisms causing diabetes. However, in vitro studies of human islets remain technically challenging, and optimal use of such precious material requires a minimum of rigor and coordination to optimize the reliability and share of the information. A detailed report of the demographics of pancreas donors and of the procedures of islet handling after isolation is important but insufficient. Correct characterization of islet basic functions (a token of quality) at the time of experimentation is also crucial. SCOPE OF REVIEW: I have analyzed the literature reporting measurements of insulin and glucagon in the human pancreas or isolated human islets. The published information is often fragmentary. Elementary features such as islet size, insulin content, or rate of hormone secretion are either unreported or incorrectly reported in many papers. Although internal comparisons between control and test groups may remain valid, comparisons with data from other laboratories are problematic. The drawbacks, pitfalls and errors of common ways of expressing hormone content or secretion rates are discussed and alternatives to harmonize data presentation are proposed. MAJOR CONCLUSIONS: Greater coherence and rigor in the report of in vitro studies using human islets are necessary to ensure optimal progress in our understanding of the pathogenesis of diabetes.